Modelagem numérica e computacional da hidrodinâmica de reservatórios utilizando as equações bidimensionais de Saint-Venant - Magro, Guilherme Resende (2018)
Accumulations or water impoundments are solutions used both for population supply and for numerous activities, including power generation and irrigation. Studies of the hydrodynamics of natural or artificial bodies of water allow for more detailed descriptions of the behavior of velocity and depth fields and are of paramount importance in order to plan the use of these resources in order to ensure sustainable and efficient utilization. There are computer programs in the market that execute hydrodynamic simulations, however, they present certain peculiarities that, although they are not limiting, require more time of learning on the part of the users. The purpose of this work is, starting from the Saint Venant equations in 2D, to produce the SimHidro2D, which is a routine of calculations made in a computer program of simple learning to make it easier and more practical to perform numerical simulations of flows. Tests were performed and the results obtained were compared with the results of other researchers for the validation of the calculation routine. Subsequently, was made the hydrodynamic simulation of the Bom Jardim Reservoir, located in the municipality of Uberlândia in the state of Minas Gerais, and obtained its fields of depths and velocities and then performed a comparative analysis of these results with the results of the simulation made with the aid of the computational tool HEC-RAS. The tool developed proved to be able to simulate the behavior of water bodies generating good results.